2015
DOI: 10.1016/s1473-3099(15)70124-6
|View full text |Cite
|
Sign up to set email alerts
|

Malaria morbidity and mortality in Ebola-affected countries caused by decreased health-care capacity, and the potential effect of mitigation strategies: a modelling analysis

Abstract: Summary Background The ongoing Ebola epidemic in parts of west Africa largely overwhelmed health-care systems in 2014, making adequate care for malaria impossible and threatening the gains in malaria control achieved over the past decade. We quantified this additional indirect burden of Ebola virus disease. Methods We estimated the number of cases and deaths from malaria in Guinea, Liberia, and Sierra Leone from Demographic and Health Surveys data for malaria prevalence and coverage of malaria interventions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
132
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(141 citation statements)
references
References 9 publications
5
132
0
1
Order By: Relevance
“…The incidence of malaria was similar in all patients, regardless of EBOV infection status, and was particularly high. This incidence is consistent with the high rates of mortality unrelated to EVD observed in forested areas of Guinea during the outbreak, with most of these deaths due to untreated malaria and measles (13)(14)(15). In contrast, no increase in mortality was associated with coinfection with P. falciparum in another study in Guinea (16), and a recent report described a reverse trend and suggested that coinfection may …”
Section: Discussionsupporting
confidence: 85%
“…The incidence of malaria was similar in all patients, regardless of EBOV infection status, and was particularly high. This incidence is consistent with the high rates of mortality unrelated to EVD observed in forested areas of Guinea during the outbreak, with most of these deaths due to untreated malaria and measles (13)(14)(15). In contrast, no increase in mortality was associated with coinfection with P. falciparum in another study in Guinea (16), and a recent report described a reverse trend and suggested that coinfection may …”
Section: Discussionsupporting
confidence: 85%
“…The health disaster resulted in severe budget cuts to non-Ebola-related health services and a significant reduction in the use of health services owing to fears of cross-infection. As a result, more people are estimated to have died from childbirth, malaria, and AIDS, as well as other diseases (Walker et al 2015).…”
Section: Public Health Needs In Disastersmentioning
confidence: 99%
“…Population-based studies of maternal health service utilization in SSA have supported the Andersen model, suggesting an appraised need for services based on predisposing factors and enabling factors (Arthur, 2012;Dixon et al, 2014;Singh et al, 2014). Yet, in the context of the Ebola epidemic, the absence of health care providers offering relevant services, the inability to differentiate between Ebola and other febrile diseases at onset, and the fear of contracting Ebola at a health facility can also prevent pregnant women from seeking reproductive health services (Davtyan et al, 2014;Walker et al, 2015;Men endez et al, 2015).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In Liberia, the stigma that was associated with pregnant women during the epidemic draws attention to a need to understand how psychosocial factors may influence health service use in context (Weiss and Ramakrishna, 2006;Link and Phelan, 2006;Walker et al, 2015;Men endez et al, 2015;Delamou et al, 2014). Consequently, this analysis is informed by Goffman's (1963) conceptualization of stigma as a powerful, discrediting and tainting social label that fundamentally changes the way individuals' view themselves or are viewed by other people.…”
Section: Theoretical Frameworkmentioning
confidence: 99%